Relationship between the Length of Sperm Tail Mitochondrial Sheath and Fertility Traits in Boars Used for Artificial Insemination - Karl Kerns; Jennifer Jankovitz; Julie Robinson; Amanda Minton; Chris Kuster; Peter Sutovsky (MDPI AG, 2020)
The length of sperm tail midpiece, occupied by the mitochondrial sheath (MS), has been correlated with reproductive traits of mice, fish, and birds; however, it is not known whether such a correlation exists in higher order species such as domestic pigs. As the mitochondria provide for sperm motility and generate the fertility-affecting reactive oxygen species (ROS), we hypothesized that MS length correlates with boar semen parameters and artificial insemination (AI) fertility. Sperm samples collected from 57 boars and used for single sire AI were labeled with ProteoStat Aggresome probe (AGG; Enzo Life Sciences) for MS imaging by epifluorescence microscopy and image-based flow cytometry (IBFC). The mean boar MS length was 7.26 ± 0.2 µm, ranging from 6.94 ± 0.18 µm to 7.65 ± 0.31 µm. The absolute longest MS measured was 9.19 µm and the shortest was 5.83 µm. Boars in the high tertile of MS length had significantly higher conception rate (CR; p = 0.05) and sperm parameters. Boars within the high tertile of average number piglets born per litter had significantly shorter MS and more varied MS length than boars in the low tertile (p = 0.04). MS length data correlated with conventional sperm parameters including percent viable and intact acrosomes (p = 0.03), basal:induced oxidation ratio (measure of intracellular ROS levels; p = 0.02) and Comp DNA (chromatin integrity; p = 0.06) along with many flow cytometric AGG parameters in IBFC. Sperm head AGG intensity median absolute deviation had a negative correlation with total born (r = −0.423 p = 0.004). These data reveal a complex relationship between sperm MS length and aggresome abundance to sperm parameters and boar reproductive success in AI service.